Latining America Black-Brown Passages and the Coloring of Latino/a Studies - Milian, Claudia (The New Southern Studies, 2013)
Claudia Milian proposes that the economies of blackness, brownness, and dark brownness summon a new grammar for Latino/a studies that she names "Latinities." Milian argues that this ensnared economy of meaning startles the typical reading practices deployed for brown Latino/a embodiment. Latining America keeps company with and challenges existent models of Latinidad, demanding a distinct paradigm that puts into question what is understood as Latino and Latina today. Milian conceptually considers how underexplored "Latin" participants-the southern, the black, the dark brown, the Central American-have ushered in a new world of "Latined" signification from the 1920s to the present.